Implementasi Manajemen Strategi Adaptasi Organisasi Sekolah Dalam Konteks Perubahan Globalisasi - Syifahayu, Syifahayu; Hidayat, Rais; Supriyanto, Dwi (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
This research aims to obtain a description of strategic management that has the advantage of adapting school organizations in the context of changing globalization at SD Negeri 1 Rejosari. The focus of this research is: (1) how to plan the strategic management of SD Negeri 1 Rejosari so that it has excellence and high competitiveness?; (2) How does school quality assurance have implications for the provision of quality education services?; (3) Is the school development strategy management appropriate to the conditions and needs of the times? This research uses a qualitative approach with a case study method. Data was collected using interview, observation and documentation techniques. Data analysis is carried out by compressing data, presenting data and drawing conclusions. Research results: (1) strategic management planning for SD Negeri 1 Rejosari using simulation, habituation and facilitation stages; (2) school quality assurance which has implications for the existence of quality education services developed through the Program Sekolah Generasi Kreatif (SENSITIF); (3) the learning flow that colors the learning process provides an overview of graduate profiles according to the conditions and needs of the times. It is necessary to use the services of educational consultants to improve the achievement of the school's vision and mission. The strategic management of SD Negeri 1 Rejosari which utilizes the use of computer informatics has succeeded in increasing student achievement. The strategic management of SD Negeri 1 Rejosari attracted the interest of parents of students to send them to SD Negeri 1 Rejosari. The strategic management of SD Negeri 1 Rejosari succeeded in increasing the number of students significantly from 2019 to 2023.